UWB-TOA geolocation techniques in indoor environments - Rashid, A. Saeed; Sabira, Khatun; Borhanuddin, Mohd. Ali; Mohd. Khazani, Abdullah (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/